PENGEMBANGAN MEDIA SICERNA (EDUKASI SISTEM PENCERNAAN MANUSIA) BERBASIS KOMIK PADA MATERI SISTEM PENCERNAAN MANUSIA KELAS 5 SEKOLAH DASAR - Ana Yulianti; Karimatus Saidah; Wahid Ibnu Zaman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to develop educational comic-based Sicerna (Human Digestive System Education) media and to determine the validity, practicality and effectiveness of the developed media.  The research method used in this research is development research (R&D) using the ADDIE model. The research subjects were 5th grade students of SDN Maduretno 1, totaling 41 students. Data collection techniques using research instruments in the form of observation and interview guidelines, questionnaires and test questions in the form of pre-test and post-test questions. The results of media validity obtained from media experts, and material experts received an average score of 91% with a very valid category. Furthermore, the results of media practicality were carried out by teachers and students. The practicality results obtained from the teacher, namely 90% with a very practical category. The results obtained from the practicality of students are 100% with a very practical category. The results of media effectiveness are the results of the Wilcoxson test which shows a significant value <0.001 which means that there is a significant difference between the results of the pretest and posttest with an average pre-test of 60 and an average post-test value of 82,8 on the material of the human digestive system in grade 5 SDN Maduretno 1. Based on these results, it can be said that the Sicerna (Educational Human Digestive System) media based on educational comics with material on the digestive system in humans is feasible to use because it has reached the standard assessment criteria of the Sicerna media.